Opening & High Level Panel: Agriculture, Landscapes and Livelihoods Day - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Filmed Live at Agriculture, Landscapes and Livelihoods Day 5, 3 December 2012 in Doha, Qatar. http://www.agricultureday.org Opening Keynote: Mr Fahad Bin Mohammed Al-Attiya, Chairman of the Qatar National Food Security Commission High Level Panel Looking forward: Identifying scalable solutions, gaps, and trade offs in addressing climate change impacts for agriculture, landscapes and livelihoods - Tony La Vina, Dean, Ateneo School of Government, The Philippines - Professor Judi Wakhungu, Executive Director of the African Centre for Technology Studies - Robert Carlson, President, World Farmers' Organisation - Dr Mahmoud Solh, Director General, International Center for Agricultural Research in the Dry Areas (ICARDA) Moderator: Dr Lindiwe Majele Sibanda, CEO FANRPAN